Au prisme de l’altérité, les orthodoxes de Beyrouth au début du xix esiècle - May Davie (Revue des Mondes Musulmans et de la Méditerranée)
The social constructs of the Orthodox of Beirut, at the beginning of the 19th century, took place as much in the framework of the community as through external networks of social and economic relations. Using urban history approaches, this article contradicts the theories of religious segregation.